Lactobacillus fermentum ZC529 Protects Intestinal Epithelial Barrier Integrity by Activating the Keap1-Nrf2 Signaling Pathway and Inhibiting the NF-κB Signaling Pathway - Zian Yuan; Lang Huang; Zhenguo Hu; Junhao Deng; Yehui Duan; Qian Jiang; Bi’e Tan; Xiaokang Ma; Chen Zhang; Xiongzhuo Tang (Antioxidants)
The probiotic bacteria Lactobacillus fermentum ZC529 (L.f ZC529) has been identified from the colon of the Diannan small-ear (DSE) pig, but its intestinal protective function still lacks investigation. Here, we established a dextran sodium sulfate (DSS)-induced intestinal oxidative stress model in both Drosophila and porcine small intestinal epithelial (IPEC-J2) cell lines to explore the anti-oxidative and anti-inflammatory effects of L.f ZC529. The data showed that the intestinal colonization of L.f ZC529 counteracted DSS-induced intestinal oxidative stress and excessive reactive oxygen species (ROS) generation by activation of the CncC pathway, a homology of the nuclear factor erythroid 2-related factor 2 (Nrf2) in mammalian systems. Moreover, L.f ZC529 supplementation prevented flies from DSS-induced intestinal barrier damage, inflammation, abnormal excretory function, and shortened lifespan. Finally, L.f ZC529 also attenuated DSS-induced intestinal injury in the IPEC-J2 cell line by activating the Keap1-Nrf2 signaling and inhibiting the NF-κB signaling pathways. Together, this study unraveled the profound intestinal protective function of L.f ZC529 and provides its potential application as a new antioxidant in improving animal intestinal health as well as in developing a new probiotic in the food industry.